An experimental study of intrusion behaviors on construction sites: The role of age and gender. (June 2019) - Shuang, Dong; Heng, Li; Skitmore, Martin; Qin, Yin
Highlights: Providing a new methodology for personal level unsafe behavior identification, assessment and modification. A bright new view for the intrusion behavior differences in terms of gender and age. An original research and application of intrusion big data in construction safety management. Abstract: Intrusion, which is the unauthorized entry to hazardous areas on a construction site, is one of the most serious rule-breaking behaviors. It has received limited research attention since existing manual safety observations cannot effectively capture large and complex intrusion related information. This paper explores how age and gender impact on various forms of intrusion behaviors on construction site. Location tracking technology combined with BIM (Building Information Modeling) was applied to identify and record intrusion behaviors of 147 construction workers over a 4 month period. The results, empirically tested by ANOVA, show that age and gender have significant interactive effects on both intrusion frequency and duration. The analysis further indicates that male site workers were more intrusive-prone than females. For both genders, middle-aged workers had significantly higher intrusion frequency than younger and older workers. Further, young workers had the lowest intrusion frequency and duration. Finally, the corresponding reasons for intrusions and the responsive management methods were sourced from interviews, including the influence of male hyper-masculine norms in construction and the implementation of targeted training for high risk individuals. The findings in this study also provide support and key insight into the use of location tracking technology for intrusion management and safety improvement in the construction industry.